Opportunities for Capacity Building to Create Healthy School Communities in the Netherlands: Focus Group Discussions With Dutch Pupils - van Dongen, Bonnie Maria; de Vries, Inge Maria; Ridder, Monica Antonia Maria; Renders, Carry Mira; Steenhuis, Ingrid Hendrika Margaretha (Frontiers in Public Health, 2021)
Background: To sustainably implement a healthy school community in which stakeholders, including pupils, feel ownership over health-promotion activities, building community capacity is important. Pupils have experiential knowledge that is complementary to professional knowledge, but their perspectives on capacity-building processes are underexposed. This study aims to explore secondary-school pupils’ perceptions about key influencers on physical activity and dietary choices and starting points for building community capacity. Methods: Seven focus groups with 41 pupils were held in four secondary schools engaged in a capacity-building intervention. Transcripts were analysed thematically regarding key influencers about choices in the home and school setting and capacity-building strategies (leadership, participation, tailored health-promotion activities and local networks). Results: Parents remained important influencers for making healthy choices, but snacking choices were increasingly made independently from parents based on attractiveness, availability and cost. Choices to engage in physical activity depended on social aspects and opportunities in the physical environment. Pupils considered their influence over the healthy school community limited, desired more involvement, but require this to be facilitated. They identified leaders mainly within formal structures, e.g. student councils. They believed health-promotion activities related to the physical environment and project-based activities within the curriculum have the maximum potential to stimulate healthy behaviours in school communities. Conclusion: This study shows that pupils can reflect critically on their physical activity and dietary choices, and on how this can contribute to processes in creating a healthy school community. In order to take an active role, they need to be considered as full partners and leadership roles should be facilitated in existing structures.